Mathematics Literacy Skill Seen from Self-Regulated Learning (SRL) in SQ4R Learning with Mathematics Realistic Approach - Nurvicalesti, Nikmah; Walid, Walid; Dewi (Nino Adhi), Nuriana Rachmani (Unnes Journal of Mathematics Education Research, 2021)
This research aimed to describe mathematics literacy sill seen from SRL at students categorized high, moderate, and poor. This research was done at VII grade of SMP Negeri 13 Semarang in academic year 2018/2019. This mix method research used sequential explanatory strategy. It is a procedure to collect quantitative and qualitative data respectively. The findings showed that mathematics literacy skill of the students on each category had different indicator of mastery and when it was seen from SRL. The differences were due to they had various developments. Therefore, the learning implementation should be in line with understanding which could be achieved by students and there was a need of self-regulation of students which were supported by environment.